Zimbabwe seed fair - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
According to findings which are the result of consultations, held within the framework of a food security project in theMasvingo province of Zimbabwe to identify the major concerns of local farmers, many traditional crop varieties havedisappeared,...